The length scale effect between wall and closes field point on a single turbine blade simulation / Mohd Hafiz Mohd Noh ... [et al.] - Mohd Noh, Mohd Hafiz; Abdul Hamid, Ahmad Hussein; Koichi, Mori (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
A numerical code has been developed based on experiment data, by using Finite Volume Method. Four different turbulence models (one equation model) have been tested; Spalart-Allmaras, Delay Eddy Simulation, Delay Detached Eddy Simulation and Improve Delayed Detached Eddy Simulation. The exit Reynolds number is 2.8  106 and the exit isentropic Mach number is 0.79. The code has been validated with isentropic Mach number around the blade, trailing edge pressure distribution, vortex shedding frequency at S/D=-0.62 and boundary layer profile at a distance equal to one. DDES has shown a good agreement qualitatively and quantitatively with the experiment as compared with others and at region -1<S/D<1, all results show insignificant different.